In recent years, there has been an increasing an abuse of slaughtered death chicken for human consumption, so it is important to find a practice ways to identify it. Experiments were conducted to determine whether the quality of meat taken from slaughtered death chicken can be detected through quality attributes of meat (Warner-Bratzler (WB) shear value, CIE L* a* b* color, and histological changes. Thirty pieces of breast (M. pectoralis) and thigh (M. biceps femoris) meat were obtained from co - Razali .; Denny W. Lukman; Srihadi Agungpriyono; Mirnawati Sudarwanto (Forum Pasca Sarjana, 2007)
In recent years, there has been an increasing an abuse of slaughtered death chicken for human consumption, so it is important to find a practice ways to identify it. Experiments were conducted to determine whether the quality of meat taken from slaughtered death chicken can be detected through quality attributes of meat (Warner-Bratzler (WB) shear value, CIE L* a* b* color, and histological changes.  Thirty pieces of breast (M. pectoralis) and thigh (M. biceps femoris) meat were obtained from commercial slaughtering house.  The samples were classified into three groups namely halal slaughtered chicken (AHS), slaughtered death chicken (AMS), and slaughtered stressed chicken (ALS) and all samples processed for microscopic observations, for WB value and color after 1, 5 and 9 h postmortem (PM).  This study showed that percentage of degenerated and necrotic muscle fibres of breast and thigh meat of AMS and ALS were significantly higher (P<0.05) than AHS.  The WB values of all samples were nearly similar (P>0.05).  The L* value of breast and thigh meat of AMS and ALS were lower whereas a* value of breast and thigh meat of AMS were significantly (P<0.05) higher than those of AHS and ALS.  The muscle fiber interstitial space had significant positive correlation with degenerated muscle fiber (P<0.001, r=0.52), necrotic muscle fiber (P<0.001, r=0.57) of breast meat, and also with degenerated muscle fiber (P<0.001, r=0.68) and necrotic muscle fiber (P<0.001, r=0.56) of thigh meat.  The biologic parameters can be used to distinguish between the slaughtered death chicken and halal slaughtered chicken.   Key words: meat quality, muscle fiber, slaughtered death chicken, L* a* b* value